On the linkage analysis modle of the telecom companies’ investment benefit - Bing XU (物联网学报)
With the end of the era of high profit growth of telecom operators,the effectiveness of basic resource investment had attracted much attention.The provincial telecom operators paied more attention to the investment efficiency of their subordinate cities,and how to achieve efficient delivery of resources was the key for provincial corporate.On the basis of the traditional evaluation methods,an index linkage analysis system from the perspective of key indicators related performance was attempted to establish,starting from benchmarking with the province's average value,and a comprehensive evaluation of the investment efficiency of the city was made.The input of resources was strived to avoid into the air,and the investment efficiency of land and city was strived to maximize.